2014
DOI: 10.1513/annalsats.201310-335oc
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microbiota Stratification System Predicts Future Exacerbations in Bronchiectasis

Abstract: Stratification of patients with non-cystic fibrosis bronchiectasis on the basis of predominant bacterial taxa is more clinically informative than either conventional culture or quantitative PCR-based analysis. Further investigation is now required to assess the mechanistic basis of these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
199
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(211 citation statements)
references
References 19 publications
10
199
2
Order By: Relevance
“…Clinical translation to date suggests that loss of diversity, with dominance of one or a few species, is associated with worse lung function and more exacerbations, and that loss of diversity may occur during exacerbations [25][26][27][28]. Overall these studies are consistent with data from culture based studies, with Pseudomonas aeruginosa dominance being associated with worse lung function and more exacerbations whether by molecular-or culture-based means and high bacterial loads of "classical" bronchiectasis pathogens being associated with higher neutrophilic inflammation and more exacerbations [28].…”
Section: The Pathophysiology Of Bronchiectasis and The Goals Of Treatmentioning
confidence: 99%
“…Clinical translation to date suggests that loss of diversity, with dominance of one or a few species, is associated with worse lung function and more exacerbations, and that loss of diversity may occur during exacerbations [25][26][27][28]. Overall these studies are consistent with data from culture based studies, with Pseudomonas aeruginosa dominance being associated with worse lung function and more exacerbations whether by molecular-or culture-based means and high bacterial loads of "classical" bronchiectasis pathogens being associated with higher neutrophilic inflammation and more exacerbations [28].…”
Section: The Pathophysiology Of Bronchiectasis and The Goals Of Treatmentioning
confidence: 99%
“…Whereas bronchiectasis can result from a variety of recognised aetiologies, it is often considered idiopathic. Recent studies have revealed a substantial and diverse bacterial microbiota (Tunney et al, 2013;Rogers et al, 2013bRogers et al, , 2014van der Gast et al, 2014), which are typically dominated by either Haemophilus influenzae or Pseudomonas aeruginosa. Perhaps unsurprisingly given its colonisation of the upper airways in healthy individuals, H. influenzae is detectable in lower airway secretions from almost all bronchiectasis patients and is commonly the numerically dominant species (Rogers et al, 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps unsurprisingly given its colonisation of the upper airways in healthy individuals, H. influenzae is detectable in lower airway secretions from almost all bronchiectasis patients and is commonly the numerically dominant species (Rogers et al, 2013b. In contrast, P. aeruginosa-dominated infections occur in a smaller number of patients but are associated with an accelerated decline in lung function, more frequent pulmonary exacerbations, greater sputum production and a higher requirement for antibiotic therapy (Evans et al, 1996;Ho et al, 1998;Shoemark et al, 2007;Rogers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms, history of exacerbations and microbiological data are frequently used to stratify the severity of patients with NCFB; however, the incorporation of imaging abnormalities into these classifications may allow for a more complete picture of the impact of the disease 52, 53. Therefore, there is great interest in the evaluation of the extent and severity of bronchiectasis more objectively using CT.…”
Section: Diagnostic Approachmentioning
confidence: 99%